Body fat changes and risk of new onset of hypertension and hyperlipidaemia among Korean adults: A longitudinal study - Jinyoung Shin; Sang-Hyun Park; Jae Hoon Cho; Tae-Eun Kim (Clinical Medicine)
Background: This study examined the association between changes in body fat, body mass index (BMI), and the risk of newly developed hypertension and hyperlipidaemia in the general population. Methods: This longitudinal study included 17,598 individuals without prior hypertension and hyperlipidaemia who underwent at least three health examinations between January 2015 and December 2022. Body fat was classified as decreased (≥ 5%), stable (within 5%), and increased (≥ 5%) using bioelectrical impedance analysis. BMIs were categorised as healthy weight/underweight (BMI < 23), overweight (23 ≤ BMI < 25), and obesity (BMI ≥ 25). Hypertension and hyperlipidaemia were identified through self-reported medication use or clinical measurements. Results: Increases in BMI or body fat were associated with higher incidence rates of hypertension and hyperlipidaemia. Decreased body fat was associated with a lower risk of hypertension in the overweight (odds ratio: 0.638, 95% confidence interval: 0.464–0.876) and obese groups (0.724, 0.577–0.909). Individuals with healthy weight/underweight with increased body fat had a higher incidence of hyperlipidaemia than individuals with overweight with decreased body fat (87.2 vs 66.4 per 1,000 people). Compared to the stable body fat group, increased body fat raised the risk of hyperlipidaemia (healthy weight/underweight: 1.522, 1.248–1.855; overweight: 1.278, 1.032–1.583; and obesity: 1.214, 1.028–1.433). Individuals living with overweight with decreased body fat demonstrated a lower risk of hyperlipidaemia (0.546, 0.400–0.747). Conclusions: Increased body fat was associated with a higher risk of hyperlipidaemia, even within the same BMI category. Decreasing body fat, particularly in individuals living with overweight, is associated with a lower risk of hypertension and hyperlipidaemia.